Effects of Silane Coupling Agents on Physical Properties of Simultaneous Biaxially Stretched Polylactide Film - Phongtamrug, Suttinun; Pilasen, Patakorn; Ridthitid, Kitiya (Applied Science and Engineering Progress, 2024)
Simultaneous biaxial stretching by using high speed was shown to improve the toughness of the polylactide (PLA) film. Additionally, a silane coupling agent was utilized to increase the mechanical strength of the product by either physical or chemical bonding. Different types of silane coupling agents influenced product properties. In this study, three types of silane coupling agents, i.e. (3-chloropropyl)trimethoxysilane (CPS), 3-aminopropyltriethoxysilane (APS), and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (DMS), were selected and compounded with PLA by using 0.1–2 phr. This work investigated the effects of the blended silane coupling agent on the physical properties of biaxially stretched PLA films. The blended PLA sheets were manufactured by using a chill-roll cast film extruder and the biaxially stretched films were prepared by a biaxial stretcher. An existing silane coupling agent in PLA films was confirmed by infrared spectroscopy and energy-dispersive X-ray analysis. Furthermore, thermal and tensile properties of the obtained films were determined. Flexibility of biaxially stretched PLA film with a diamino silane coupling agent was increased while its stiffness was maintained. Elongation at break of the biaxially stretched PLA film blending with DMS was increased more than 2 times. Moreover, oxygen gas permeability and water vapor permeability of the biaxially stretched PLA films with 2 phr of APS and CPS were increased compared to those of the neat one. This work provided the structural effect of coupling agents on the physical properties of biaxially stretched PLA film.